Razpoke v slonokoščenem stolpu: literarni esteticizem in politika - Debeljak, Aleš (Teorija in praksa, 1998)
In this article the author demonstrates how is aestheticism as an artistic practice and academic theory, despite the claims to opposite, linked to the social-historical and political reality. Based on the concise analysis of selected key moments in post-World War II Slovenian culture, the author rejects aestheticism to the extent that it is understood as an ivory tower of textuality. In the light of reflections on two books by contemporary Slovenian poets whose reputation derived from their excellent command of form and style, yet they nonetheless rose in substance to the challange of the wars of disintegrated Jugoslavia, the author suggests that it is possible to maintain the dialectics of aesthetic and political without compromising artistic standards.
Keywords: esteticizem; književnost; literature; slovenska poezija; politics; politika